Are experience and schooling complementary? evidence from migrants' assimilation in the Bangkok labor market - Yamauchi, Futoshi (Elsevier, 2004)
This paper models the assimilation process of migrants and shows evidence of the complementarity between their destination experience and upon-arrival human capital. Bayesian learning is assessed, using panel data of wages from Bangkok, Thailand. It is found that (i) schooling returns are lower for migrants than for natives, (ii) the accumulation of destination experience raises wages for migrants, (iii) the experience effect is greater for more educated agents and (iv) the complementarity increases as destination experience accumulates. The results imply that more educated migrants have higher learning efficiency and can perform tasks of greater complexity, ultimately yielding higher wage growth in the destination market. -- Author's Abstract